Analysis of Individual <semantics><mstyle mathvariant="bold"><mover accent="true">V˙</mover></mstyle></semantics>O2max Responses during a Cardiopulmonary Exercise Test and the Verification Phase in Physically Active Women - Pasquale J. Succi; Brian Benitez; Minyoung Kwak; Haley C. Bergstrom (Journal of Functional Morphology and Kinesiology, 2023)
This study aimed to investigate the test–retest reliability, mean, and individual responses in the measurement of maximal oxygen consumption (<semantics><mover accent="true">V˙</mover></semantics>O2max) during a cardiopulmonary exercise test (CPET) and the verification phase during cycle ergometry in women. Nine women (22 ± 2 yrs, 166.0 ± 4.5 cm, 58.6 ± 7.7 kg) completed a CPET, passively rested for 5 min, and then completed a verification phase at 90% of peak power output to determine the highest <semantics><mover accent="true">V˙</mover></semantics>O2 from the CPET (<semantics><mover accent="true">V˙</mover></semantics>O2CPET) and verification phase (<semantics><mover accent="true">V˙</mover></semantics>O2verification) on 2 separate days. Analyses included a two-way repeated measures ANOVA, intraclass correlation coefficients (ICC2,1), standard errors of the measurement (SEM), minimal differences (MD), and coefficients of variation (CoV). There was no test (test 1 versus test 2) × method (CPET vs. verification phase) interaction (p = 0.896) and no main effect for method (p = 0.459). However, test 1 (39.2 mL·kg−1·min−1) was significantly higher than test 2 (38.3 mL·kg−1·min−1) (p = 0.043). The <semantics><mover accent="true">V˙</mover></semantics>O2CPET (ICC = 0.984; CoV = 1.98%; SEM = 0.77 mL·kg−1·min−1; MD = 2.14 mL·kg−1·min−1) and <semantics><mover accent="true">V˙</mover></semantics>O2verification (ICC = 0.964; CoV = 3.30%; SEM = 1.27 mL·kg−1·min−1; MD = 3.52 mL·kg−1·min−1) demonstrated “excellent” reliability. Two subjects demonstrated a test 1 <semantics><mover accent="true">V˙</mover></semantics>O2CPET that exceeded the test 2 <semantics><mover accent="true">V˙</mover></semantics>O2CPET, and one subject demonstrated a test 1 <semantics><mover accent="true">V˙</mover></semantics>O2verification that exceeded the test 2 <semantics><mover accent="true">V˙</mover></semantics>O2verification by more than the respective CPET and verification phase MD. One subject demonstrated a <semantics><mover accent="true">V˙</mover></semantics>O2CPET that exceeded the <semantics><mover accent="true">V˙</mover></semantics>O2verification, and one subject demonstrated a <semantics><mover accent="true">V˙</mover></semantics>O2verification that exceeded the <semantics><mover accent="true">V˙</mover></semantics>O2CPET by more than the MD. These results demonstrate the importance of examining the individual responses in the measurement of the <semantics><mover accent="true">V˙</mover></semantics>O2max and suggest that the MD may be a useful threshold to quantify real individual changes in <semantics><mover accent="true">V˙</mover></semantics>O2.